2011
DOI: 10.3748/wjg.v17.i16.2120
|View full text |Cite
|
Sign up to set email alerts
|

MELD score can predict early mortality in patients with rebleeding after band ligation for variceal bleeding

Abstract: This study demonstrated that the MELD score is an easy and powerful predictor for 6-wk mortality and outcomes of patients with early rebleeding after EVL for EVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 17 publications
5
31
1
Order By: Relevance
“…In univariate analysis clot on varix, serum bilirubin, CTP score and MELD score were predictive indicators of rebleeding within 6 weeks. Independent risk factors that predicts early rebleeding in multivariate analysis were clot on varix (P < 0.0001, OR = 11.6, 95% CI: 2.87 -47.29) and serum bilirubin (P < 0.05, OR = 1.1, 95% CI: 1.02 -1.19), which was consistent with other studies [3] [12] [13] [16] [17]. D'Amico et al [18], demonstrated that active bleeding at endoscopy is only independent predictor of early rebleeding, but not of death, while in our study clot on varix was independent predictor of early rebleeding.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In univariate analysis clot on varix, serum bilirubin, CTP score and MELD score were predictive indicators of rebleeding within 6 weeks. Independent risk factors that predicts early rebleeding in multivariate analysis were clot on varix (P < 0.0001, OR = 11.6, 95% CI: 2.87 -47.29) and serum bilirubin (P < 0.05, OR = 1.1, 95% CI: 1.02 -1.19), which was consistent with other studies [3] [12] [13] [16] [17]. D'Amico et al [18], demonstrated that active bleeding at endoscopy is only independent predictor of early rebleeding, but not of death, while in our study clot on varix was independent predictor of early rebleeding.…”
Section: Discussionsupporting
confidence: 91%
“…Early rebleeding and mortality rate increase sharply within 6 weeks period then stabilized. Early rebleeding rate in the current study was 25.5%, a similar result reported by Krige et al [12] but it is slightly higher than that in some other studies [3] [13] while it is lower than that in other studies [14] [15].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…117 MELD score is also a powerful predictor for mortality at 6 weeks for patients who develop early rebleeding after endoscopic variceal ligation. 118 Comparison of CTP and MELD scores in predicting outcome of VH have shown discrepant data with similar prediction in one study 119 while CTP to be better predictor compared to MELD in another study. 120 …”
Section: Variceal Bleedingmentioning
confidence: 94%